Aktualisasi Hukum Agraria Guna Menunjang Otonomi Daerah - Winahyu Erwiningsih (Jurnal Hukum IUS QUIA IUSTUM, 2000)
The Enactmen ofRegional Autonomy for the Huge land territory to the district Area is basically stated as the claim of reformation. It also become the main clue for the regional autonomy. Both ofthem were endorsed in the Basic Principle of Agrarian Law (UUPA). Theland territory in the whole nation was revealed and endorsed in the form of justice to the society in this regulation. It also have another main purpose a for the growth of prosperity. But in fact, the condition of land territory is being far from the basic purpose and claim. The question now is all about the eficlency of Basic Principle of Agrarian Law to hold the regional autonomy.